Implementasi Database Auditing dengan Memanfaatkan Sinkronisasi DBMS - Abhisena, Gede Anantaswarya; Sukarsa, I Made; Githa, Dwi Putra (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2017)
Database auditing can be an important component in database security and governance regulations. Database Administrator needs to be more alert in the methods used to maintain the corporate data, and standards and requirements available against available data. At high level, databases auditing are facility to search the usage of database authority and resources. When auditing is active, every database operation that audited generates an audit trails of the information changes made. Database synchronization is a form of replication, which is a process to convincing every copy of database comprise the same data. Database synchronization allows to utilized many purposes, one of which builds auditing that records every activities occur at database. The audit trails from the resulting of data operations allows DBAs (Database Administrators) maintained audit trails time to time, to perform an analysis of access patterns and modifications to data in DBMS (Database Management System).